Impact of COVID-19 vaccination on adolescent and youth students’ mental health and bullying behaviors after the lifting of COVID-19 restrictions in China - Song, Hong-Jun; Wang, Cong; Mu, Yun-Fei; Cai, Jia; Deng, Zhongyue; Wang, Yu; Deng, Ai-Ping; Liu, Ting; Li, Bin; Huang, Yi; Chen, Jin; Hu, Yan; et al. (Frontiers in Public Health, 2024)
BackgroundVaccination plays an important role in fighting against COVID-19. However, it is unclear about the association among vaccination, mental health, and bullying behaviors in China.MethodThis online survey was conducted to investigate the association among vaccination status, mental health problems and bullying behaviors in students from December 14, 2022 to February 28, 2023 in Sichuan, China. All participants (N = 82,873) were adolescents recruited via their teachers and professors. Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), PTSD Checklist for DSM-5 (PCL-5), Sleep Severity Index Scale (ISI) and Cyberbullying behaviors were tested.ResultsThe rates of depression, anxiety and PTSD in participants without vaccination were significantly higher than that in those with vaccination. Moreover, participants with more doses of vaccines had significantly lower rates of depression, anxiety, PTSD, school and cyber bullying (p < 0.001). The rates of homosexual orientation, drinking, smoking were higher in participants with three or more doses of vaccines than those with less doses of vaccines (p < 0.001).ConclusionThis study suggests that COVID-19 vaccination will not only protect students’ physical health, but also improve mental health. It is crucial to explore the mechanism between vaccination and mental health problems and bullying behaviors in further studies.